2016
DOI: 10.1589/jpts.28.1998
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of upper extremity function, pain, and tactile sense between the uneffected side of hemiparetic patients and healthy subjects

Abstract: [Purpose] The aim of this study was to compare the unaffected upper extremity of patients with hemiparesis with that of healthy subjects in terms of function, pain, and tactile sense. [Subjects and Methods] Upper extremity evaluation parameters of 20 patients with hemiparesis were compared with an age-matched control group of 20 healthy subjects. A shorter version of the Disability of Arm and Shoulder Questionnaire, Upper Extremity Functional Index, and Simple Shoulder Test were used to evaluate the upper extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…It was determined that the pain values were higher in the intact side upper extremities of the hemiplegic patients. This supports our observation of an increase in pain levels in the intact side upper extremities of the patients with stroke after the one-month follow-up period [6].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It was determined that the pain values were higher in the intact side upper extremities of the hemiplegic patients. This supports our observation of an increase in pain levels in the intact side upper extremities of the patients with stroke after the one-month follow-up period [6].…”
Section: Discussionsupporting
confidence: 91%
“…Stroke involves the rapid loss of brain function due to a disturbance in blood flow to the brain and often affects upper extremity mobility [6]. In the majority of A -Research concept and design B -Collection and/or assembly of data C -Data analysis and interpretation D -Writing the article E -Critical revision of the article F -Final approval of article patients with stroke (more than 50%), functional disability occurs in the upper extremity.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is relevant evidence that also the unaffected hands might undergo functional changes after stroke. 26 , 27 Therefore, our models included the motor function of the unaffected hand as independent covariates. Post hoc , we evaluated how the models for CST FA AH would perform in reduced models with proportional grip force and pinch force values (affected hand/unaffected hand) as the dependent variables.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of arms functions is a major problem that causes long-term impairment, which affects 30%-66% of all stroke cases (26). Balci et al found significant difference between hemiplegic patients' and healthy individuals' upper extremity functions (27). Few studies have objectively and quantitatively evaluated the upper and lower extremities of patients participating in a rehabilitation program (18).…”
Section: Discussionmentioning
confidence: 99%